A glove material with enhanced puncture resistance and preparation method thereof
Patent Information
- Application Number
- CN202411556201.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Surgical gloves are prone to needle rupture during operation, and invisible perforation may lead to blood-borne pathogen transmission and infection at the surgical site. The existing glove materials are insufficient to resist punctures.
Use a glove material that enhances thorns resistance. By mixing the stabilizer of thorns and polyvinyl chloride paste, p -benanamate, stabilizer, and tougher reduced adhesive solvents to prepare a nano -shell structure Purching, improving the thorns to resistance of gloves.
It significantly improves the thorns tolerance of gloves, can resist acupuncture, enhance the stretching ability and anti -penetration performance of gloves, and increases the anti -thorns effect of about 4.6 times compared to the blank group.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a glove material with enhanced stab resistance and a preparation method thereof. Background Art
[0002] The integrity of surgical gloves as a protective barrier benefits both the surgical team and the surgical patient. However, during surgery, gloves are often punctured by needles without being visibly detected. Invisible punctures can lead to the transmission of bloodborne pathogens to surgical team members and surgical site infections to patients. Therefore, improving the puncture resistance of gloves is critical. Summary of the invention
[0003] In view of this, the present invention aims to provide a glove material with enhanced stab resistance and a preparation method thereof to solve the above problems.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] A glove material with enhanced stab resistance comprises the following raw materials in parts by weight: 600-800 parts of polyvinyl chloride paste resin, 100-300 parts of stab-resistant rare earth filler slurry, 400-700 parts of dibutyl terephthalate, 5-20 parts of stabilizer and 6-30 parts of toughening and viscosity reducing solvent; wherein the stab-resistant rare earth filler slurry is obtained by mixing the stab-resistant rare earth filler with a solvent, and the stab-resistant rare earth filler comprises cyanuric acid, glycerol, cerium salt, ammonia water and a long-chain alkane ionic surfactant.
[0006] Furthermore, the raw materials of the thorn-resistant rare earth filler include, by weight, 10-15 parts of cyanuric acid, 2-4 parts of glycerol, 8-12 parts of cerium salt, 15-30 parts of ammonia water and 1-3 parts of a long-chain alkane ionic surfactant, and the mass concentration of the ammonia water is 20-29%.
[0007] Furthermore, the cerium salt is at least one of nitrate, halide, sulfate or oxalate.
[0008] Furthermore, the cerium salt is cerium chloride.
[0009] Furthermore, the solvent is ethylene glycol and hexadecyltrimethylammonium bromide, and the weight proportions of the thorn-resistant rare earth filler, ethylene glycol and hexadecyltrimethylammonium bromide are: 120-350:730-1000:8-15.
[0010] Further, the thorn-resistant rare earth filler is prepared by the following method:
[0011] 1) uniformly mixing cerium salt, cyanuric acid and glycerol, adding ammonia water thereto, and then adding a long-chain alkane ionic surfactant, stirring under heating conditions, and cooling to room temperature after the reaction is completed to obtain a mixture;
[0012] 2) placing the obtained mixture into the inner liner and reacting it in an autoclave, and obtaining an intermediate after the reaction is completed;
[0013] 3) The obtained intermediate is filtered, dried and calcined to obtain a thorn-resistant rare earth filler.
[0014] Further, the heating temperature in step 1) is 70-100°C and the stirring time is 2-4 hours;
[0015] The material of the lining in step 2) is polytetrafluoroethylene, the reaction temperature is 150-200°C, and the time is 1-4 hours;
[0016] The calcination temperature in step 3) is 500-700°C, the time is 2-5 hours, and the heating rate is 5-10°C / min.
[0017] Furthermore, the long-chain alkane ionic surfactant is any one of sodium dodecylbenzenesulfonate, cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, dodecyltrimethylammonium bromide and sodium dodecyl sulfate.
[0018] The present invention also provides a method for preparing the glove material with enhanced stab resistance as described above, the method comprising the following steps:
[0019] 1) Preparation of thorn-resistant rare earth fillers
[0020] The cerium salt, cyanuric acid and glycerol are uniformly mixed, ammonia water is added thereto, and then a long-chain alkane ionic surfactant is added thereto, and the mixture is stirred under heating conditions, and after the reaction is completed, the mixture is cooled to room temperature to obtain a mixture; the obtained mixture is placed in an inner liner, and reacted in an autoclave to obtain an intermediate after the reaction is completed; the obtained intermediate is filtered, dried and calcined to obtain a thorn-resistant rare earth filler;
[0021] 2) Preparation of thorn-resistant rare earth filler slurry
[0022] Take the thorn-resistant rare earth filler, add ethylene glycol and hexadecyltrimethylammonium bromide, stir evenly, and then sand grind to obtain;
[0023] 3) The polyvinyl chloride paste resin, the stab-resistant rare earth filler slurry, dibutyl terephthalate, a stabilizer and a toughening and viscosity-reducing solvent are mixed to obtain a slurry, which is a glove material with enhanced stab resistance.
[0024] The present invention also provides an application of the glove material with enhanced stab resistance as described above, wherein a glove model is immersed in a slurry of the glove material with enhanced stab resistance for 6 hours, and then taken out and baked for plasticization to obtain a hand model; then the hand model is immersed in a polyurethane slurry, and finally baked to obtain a glove.
[0025] Compared with the prior art, the glove material with enhanced stab resistance and the preparation method thereof of the present invention have the following advantages:
[0026] (1) The thorn-resistant rare earth filler of the present invention is synthesized from long-chain alkane ionic surfactant, cyanuric acid, glycerol and cerium salt as raw materials. After alkalization, rare earth cerium and cyanuric acid form a triazine ring with a coordination bond. The long-chain alkane ionic surfactant has a long chain, which will be at the end of the triazine ring during the initial thermal polymerization process, so that the end position of the triazine ring forms a large steric hindrance, hindering further high-temperature polycondensation reaction. Therefore, the two work together to form a stable nanosheet structure.
[0027] (2) Attaching the nanosheet structure to the surface of the glove can resist needle puncture and enhance the gloves' puncture resistance. Incorporating metal ions into nanosheets usually has better properties and a more complete sheet structure. Rare earth, as a popular "industrial vitamin" element, has outstanding performance in the field of chemical materials. To this end, in the nanosheet structure, rare earth ions are used as bridges to connect molecules in the polymerization reaction, promote structural stability, and improve the anti-puncture effect.
[0028] (3) After the glove material with enhanced puncture resistance of the present invention is loaded on the gloves, the stretching ability and puncture resistance of the gloves are improved, among which the CCL gloves are improved by about 4.6 times compared with the blank. DETAILED DESCRIPTION
[0029] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Cyanuric acid, glycerol, sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, and aqueous ammonia (NH3·H2O) were purchased from Beijing Chemical Plant (Beijing, China). La(NO3)3·6H2O, Ce(NO3)3·6H2O, Gd(NO3)3·6H2O, Sm(NO3)3·6H2O, LaCl3·7H2O, CeCl3·6H2O, GdCl3·6H2O, SmCl3·6H2O, La2(SO4)3·8H2O, Ce2(SO4)3·4H2O, Gd2(SO4)3·8H2O, Sm2(SO4)3·8H2O, La2(C2O4)3·10H2O, Ce2(C2O4)3, Gd2(C2O4)3·10H2O, and Sm2(C2O4)3·10H2O were purchased from MacLean Reagent Co., Ltd. All chemicals were used without further treatment. Distilled water (ρ = 18.2 MΩ•cm, 25°C) was from Millipore milli-Q water purification system.
[0032] Example 1
[0033] A glove material with enhanced stab resistance is prepared by the following method:
[0034] 1) Preparation of thorn-resistant rare earth fillers
[0035] Dissolve 100g of cyanuric acid in 50L of pure water, then add 30g of glycerol, stir evenly, add 100g of cerium chloride hexahydrate and stir to dissolve, then use a separatory funnel to drop 170ml of 28% ammonia water, then add 10g of sodium dodecylbenzene sulfonate and stir at 80°C for 3 hours, wait for the reaction to cool to room temperature, and obtain a mixture;
[0036] The mixture was placed in a polytetrafluoroethylene liner, and then placed in an autoclave, reacted at 180°C for 3 hours to obtain an intermediate; the intermediate was filtered, and the filter residue was dried to obtain a dry intermediate powder, and then the intermediate powder was added to a crucible, placed in a muffle furnace, and calcined at 600°C for 3 hours at a heating rate of 2°C / min to prepare a puncture-resistant filling material. The material synthesized according to this method is named CCL.
[0037] 2) Preparation of thorn-resistant rare earth filler slurry
[0038] Take 250g of thorn-resistant rare earth filler CCL, add 750mL of ethylene glycol, add 10g of hexadecyltrimethylammonium bromide, and stir evenly; then use a sand mill for sand grinding, fill the sand grinding cavity with 80% zirconium dioxide sand grinding beads, the radius of the grinding beads is 0.5mm, the sand grinding speed is adjusted to 3200rpm, the temperature of the sand grinding outlet and the sand grinding cavity is controlled at 25°C, and the sand grinding time is 5 hours.
[0039] 3) 700 g of polyvinyl chloride paste resin, 240 g of thorn-resistant rare earth filler slurry, 500 g of dibutyl terephthalate, 10 g of stabilizer and 10.5 g of toughening and viscosity-reducing solvent were mixed to obtain slurry.
[0040] The glove model is immersed in the slurry for 6 hours, and then taken out and baked for plasticization to obtain a hand mold; then the hand mold is immersed in polyurethane slurry, and finally baked to obtain a PVC glove.
[0041] Example 2
[0042] A glove material with enhanced stab resistance is prepared by the following method:
[0043] 1) Preparation of thorn-resistant rare earth fillers
[0044] Dissolve 120g of cyanuric acid in 50L of pure water, then add 35g of glycerol, stir evenly, add 90g of cerium chloride hexahydrate and stir to dissolve, then use a separatory funnel to drop 190ml of 28% ammonia water, then add 12g of sodium dodecylbenzene sulfonate and stir at 80°C for 3 hours, wait for the reaction to cool to room temperature, and obtain a mixture;
[0045] The mixture was placed in a polytetrafluoroethylene liner, and then placed in an autoclave, reacted at 180°C for 3 hours to obtain an intermediate; the intermediate was filtered, and the filter residue was dried to obtain a dry intermediate powder, and then the intermediate powder was added to a crucible, placed in a muffle furnace, and calcined at 600°C for 3 hours at a heating rate of 2°C / min to prepare a thorn-resistant filling material. The material synthesized according to this method is named CCL'.
[0046] 2) Preparation of thorn-resistant rare earth filler slurry
[0047] Take 250g of thorn-resistant rare earth filler CCL, add 750mL of ethylene glycol, add 10g of hexadecyltrimethylammonium bromide, and stir evenly; then use a sand mill for sand grinding, fill the sand grinding cavity with 80% zirconium dioxide sand grinding beads, the radius of the grinding beads is 0.5mm, the sand grinding speed is adjusted to 3200rpm, the temperature of the sand grinding outlet and the sand grinding cavity is controlled at 25°C, and the sand grinding time is 5 hours.
[0048] 3) 650 g of polyvinyl chloride paste resin, 360 g of thorn-resistant rare earth filler slurry, 550 g of dibutyl terephthalate, 15 g of stabilizer and 25 g of toughening and viscosity-reducing solvent were mixed to obtain slurry.
[0049] The glove model is immersed in the slurry for 6 hours, and then taken out and baked for plasticization to obtain a hand mold; then the hand mold is immersed in polyurethane slurry, and finally baked to obtain a PVC glove.
[0050] Example 3
[0051] On the basis of the above Example 1, glove materials and gloves with enhanced puncture resistance were prepared, and the cerium salts were replaced with Ce(NO3)3·6H2O, Ce2(SO4)3·4H2O, and Ce2(C2O4)3, respectively. The prepared rare earth fillers were named CNO, CSO, and CCO, respectively, and the cerium element was abbreviated as C.
[0052] Comparative Example 1
[0053] On the basis of the above Example 1, glove materials and gloves with enhanced stab resistance were prepared, the rare earth cerium was replaced by lanthanum, gadolinium or samarium, the rare earth salt was rare earth nitrate, rare earth halide, rare earth sulfate and rare earth oxalate, and the cerium salt was replaced by the following:
[0054] Table 1 List of rare earth salts
[0055]
[0056] According to the same experimental steps as in Example 1, oxalate anion series samples: LCO, GCO, SCO; nitric acid series samples: LNO, GNO, SNO; chloride series samples: LCL, GCL, SCL; sulfuric acid series samples: LSO, GSO, SSO were prepared. Among them, lanthanum is abbreviated as L; gadolinium is abbreviated as G; and samarium is abbreviated as S.
[0057] Comparative Example 2 Comparison of different surfactants
[0058] Solution (1):
[0059] On the basis of Example 1, sodium dodecylbenzenesulfonate was replaced with hexadecyltrimethylammonium bromide to prepare a thorn-resistant filling material CCL-1, and other operations were the same as in Example 1 to prepare a glove material and gloves with enhanced thorn resistance.
[0060] Solution (2):
[0061] On the basis of Example 1, sodium dodecylbenzene sulfonate was replaced with hexadecyltrimethylammonium chloride to prepare a thorn-resistant filling material CCL-2, and other operations were the same as in Example 1 to prepare a glove material and gloves with enhanced thorn resistance.
[0062] Solution (3):
[0063] On the basis of Example 1, sodium dodecylbenzenesulfonate was replaced with dodecyltrimethylammonium bromide to prepare the thorn-resistant filling material CCL-3, and other operations were the same as in Example 1 to prepare the glove material and gloves with enhanced thorn resistance.
[0064] Solution (4):
[0065] On the basis of Example 1, sodium dodecylbenzene sulfonate was replaced with sodium dodecyl sulfate to prepare the stab-resistant filling material CCL-4, and other operations were the same as in Example 1 to prepare glove materials and gloves with enhanced stab resistance.
[0066] Solution (5):
[0067] On the basis of Example 1, sodium dodecylbenzene sulfonate was replaced with sodium dioctyl sulfosuccinate to prepare a thorn-resistant filling material CCL-5, and other operations were the same as in Example 1 to prepare a glove material and gloves with enhanced thorn resistance.
[0068] Comparative Example 3: No rare earth added
[0069] On the basis of Example 1, a thorn-resistant rare earth filler was prepared without adding any rare earth material to obtain a thorn-resistant filling material CCL-0. Other operations were the same as in Example 1 to prepare a glove material and gloves with enhanced thorn resistance.
[0070] Experimental test:
[0071] Blank control group: 700g of polyvinyl chloride paste resin, 500g of dibutyl terephthalate, 10g of stabilizer and 10.5g of toughening and viscosity-reducing solvent were mixed to obtain slurry; the glove model was immersed in the slurry for 6 hours, and then baked and plasticized to obtain a hand mold; then the hand mold was immersed in polyurethane slurry, and finally baked to obtain PVC gloves.
[0072] 1. Perform tensile tests on various gloves, including the following steps:
[0073] The test instrument is the i-MEDITEK 1300, a Labthink pharmaceutical packaging performance tester. Six gloves of each embodiment and comparative example are taken, and three gloves are filled with water to simulate the stretched state after use. The water filling process is as follows: after the gloves are washed with clean water, 400 mL of pure water is filled into the gloves to generate a pressure of 25 cm of water column at the top of the middle finger of the gloves. The gloves filled with water are hung for 4 hours, and then the water is poured out and dried for use. The gloves that are not filled with water are washed, dried and used for use. Then each glove is cut into a dumbbell shape, and then placed in the instrument respectively, and the test is started. The results are counted and the average value of three groups is taken.
[0074] Table 2 Tensile test results of oxalic acid series gloves of Example 3 and Comparative Example 1
[0075]
[0076] Table 3 Tensile test results of nitric acid series gloves of Example 3 and Comparative Example 1
[0077]
[0078] Table 4 Tensile test results of sulfuric acid series gloves of Example 3 and Comparative Example 1
[0079]
[0080] Table 5 Tensile test results of chloride series gloves of Examples 1-3 and Comparative Example 1
[0081]
[0082] Table 6 Tensile test results of gloves prepared in Example 1 and Comparative Examples 2-3
[0083]
[0084] From the tensile test results in Table 2-5, it can be seen that the gloves with cerium salts added in the oxalic acid series, nitric acid series, sulfuric acid series and chloride series have better tensile strength and elongation at break, and cerium chloride among the cerium salts has the best effect and has the strongest tensile strength. For example, the CCL group is 1.55 times that of the blank control group.
[0085] It can be seen from Table 6 that when long-chain alkane ionic surfactants such as sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and sodium dodecyl sulfate are used, their various properties are much better than those of short-chain alkane ionic surfactants (such as sodium dioctyl sulfosuccinate), because there are long chains in long-chain alkane ionic surfactants, which will be at the end of the triazine ring during the initial thermal polymerization process, so that the end position of the triazine ring forms a large steric hindrance, hindering further high-temperature polycondensation reaction, so the two work together to form a stable nanosheet structure. In addition, too long alkane chains will cause excessive steric hindrance during high-temperature polymerization, hindering the formation of triazine rings, and ultimately unable to prepare a two-dimensional structure. In addition, when sodium dodecylbenzene sulfonate is used, the corresponding gloves have the best tensile and fracture properties, proving that among these long-chain alkane ionic surfactants, the steric hindrance formed by sodium dodecylbenzene sulfonate is the most stable, so the tensile and fracture resistance is the strongest. In addition, the comparison between CCL and CCL-0 proves that rare earth elements play a vital role in glove additives, greatly improving the puncture resistance of gloves.
[0086] 2. Conduct puncture resistance tests on various gloves using rare earth halogen salts, including the following steps:
[0087] The experimental instrument also uses the packaging performance tester i-MEDITEK 1300, and uses a 6# injection needle for puncture. Based on the above test results, gloves with puncture-resistant rare earth fillers of LCL, CCL, GCL, SCL and gloves of Comparative Examples 2 and 3, such as fingertips and palms, which are prone to perforation and damage, are selected, and 1.5×1.5cm samples are cut and installed in the puncture fixture placed on the base of the instrument. Install the injection needle on the upper moving axis of the instrument, click "Start Test", the instrument starts testing, records the maximum force value during the puncture process, and takes the average value of three groups.
[0088] Table 7 Puncture resistance test of gloves with puncture-resistant rare earth fillers of LCL, CCL, GCL and SCL
[0089]
[0090] Table 8 Anti-puncture test of gloves of Example 1, Comparative Examples 2 and 3
[0091]
[0092] It can be seen from Table 7 that the gloves with added puncture-resistant rare earth filler CCL have the best puncture resistance, which is 4.6 times that of the blank group. The rest are also more puncture-resistant than the blank group, proving that the gloves have stronger puncture resistance after adding puncture-resistant rare earth fillers containing cerium salts.
[0093] It can be seen from Table 8 that the gloves prepared by adding sodium dodecylbenzene sulfonate have the strongest puncture resistance, and the gloves without adding rare earth have reduced puncture resistance.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A glove material with enhanced stab resistance, characterized in that: The invention comprises the following raw materials in parts by weight: 600-800 parts of polyvinyl chloride paste resin, 100-300 parts of thorn-resistant rare earth filler slurry, 400-700 parts of dibutyl terephthalate, 5-20 parts of stabilizer and 6-30 parts of toughening and viscosity-reducing solvent; wherein the thorn-resistant rare earth filler slurry is obtained by mixing the thorn-resistant rare earth filler with a solvent, and the thorn-resistant rare earth filler comprises cyanuric acid, glycerol, cerium salt, ammonia water and a long-chain alkane ionic surfactant; The raw materials of the thorn-resistant rare earth filler include 10-15 parts of cyanuric acid, 2-4 parts of glycerol, 8-12 parts of cerium salt, 15-30 parts of ammonia water and 1-3 parts of long-chain alkane ionic surfactant by weight, and the mass concentration of ammonia water is 20-29%; The solvent is ethylene glycol and hexadecyltrimethylammonium bromide, and the weight proportions of the thorn-resistant rare earth filler, ethylene glycol and hexadecyltrimethylammonium bromide are: 120-350:730-1000:8-15; The long-chain alkane ionic surfactant is any one of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide and sodium dodecyl sulfate; The thorn-resistant rare earth filler is prepared by the following method: 1) uniformly mixing cerium salt, cyanuric acid and glycerol, adding ammonia water thereto, and then adding a long-chain alkane ionic surfactant, stirring under heating conditions, and cooling to room temperature after the reaction is completed to obtain a mixture; 2) placing the obtained mixture into the inner liner and reacting it in an autoclave, and obtaining an intermediate after the reaction is completed; 3) The obtained intermediate is filtered, dried and calcined to obtain a thorn-resistant rare earth filler.
2. The glove material with enhanced stab resistance according to claim 1, characterized in that: The cerium salt is at least one of nitrate, halide, sulfate or oxalate.
3. The glove material with enhanced stab resistance according to claim 2, characterized in that: The cerium salt is cerium chloride.
4. The glove material with enhanced stab resistance according to claim 1, characterized in that: The heating temperature in step 1) is 70-100°C and the stirring time is 2-4 hours; The material of the lining in step 2) is polytetrafluoroethylene, the reaction temperature is 150-200°C, and the time is 1-4 hours; The calcination temperature in step 3) is 500-700°C, the time is 2-5 hours, and the heating rate is 5-10°C / min.
5. A method for preparing a glove material with enhanced stab resistance according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: 1) Preparation of thorn-resistant rare earth fillers The cerium salt, cyanuric acid and glycerol are uniformly mixed, ammonia water is added thereto, and then a long-chain alkane ionic surfactant is added thereto, and the mixture is stirred under heating conditions, and after the reaction is completed, the mixture is cooled to room temperature to obtain a mixture; the obtained mixture is placed in an inner liner, and reacted in an autoclave to obtain an intermediate after the reaction is completed; the obtained intermediate is filtered, dried and calcined to obtain a thorn-resistant rare earth filler; 2) Preparation of thorn-resistant rare earth filler slurry Take the thorn-resistant rare earth filler, add ethylene glycol and hexadecyltrimethylammonium bromide, stir evenly, and then sand grind to obtain; 3) The polyvinyl chloride paste resin, the stab-resistant rare earth filler slurry, dibutyl terephthalate, a stabilizer and a toughening and viscosity-reducing solvent are mixed to obtain a slurry, which is a glove material with enhanced stab resistance.
6. An application of the glove material with enhanced stab resistance according to any one of claims 1 to 4, characterized in that: The glove model is immersed in the slurry of the glove material with enhanced stab resistance for 6 hours, and then baked and plasticized to obtain a hand mold; the hand mold is then immersed in the polyurethane slurry and finally baked to obtain the glove.
Citation Information
Patent Citations
Preparation method of thin PVC gloves
CN108192238A
High-elasticity PVC glove composition with extremely low precipitation, and method for preparing gloves
CN111909473A